Media dan Terorisme di Uni Eropa: - Muhammad Ahalla Tsauro (Indonesia Center for Middle East Studies, 2017)
This paper aims to describe the relations between media and terrorism that are mutually influenced and mutually beneficial. The case studies taken are a series of terror in Paris (2015) and the Manchester (2017) bombing as these two cases became global issues involving global news networks. By implementing CNN Effect theory and media analysis, the author found that the global news corporates benefited from the terrorist actions, and vice versa, the media is an important tool for terror groups to expand their influence and threats on the global community. The advancement of information technology makes the media, consciously or unconsciously, becomes the 'best friend' for the terrorist group because of its role in spreading the terrorist’ message.